A randomized dismantling trial of the open and engaged components of acceptance and commitment therapy in an online intervention for distressed college students. (March 2020) - Levin, Michael E.; Krafft, Jennifer; Hicks, Elizabeth T.; Pierce, Benjamin; Twohig, Michael P.
Abstract: This dismantling trial compared the effects of a full online Acceptance and Commitment Therapy (ACT) intervention to the isolated effects of the Open (i.e., acceptance, cognitive defusion) and Engaged (i.e., values, committed action) components of ACT. A sample of 181 distressed college students were randomized to one of four conditions: a 12-session full ACT website (Full), a version targeting the Open components (Open), a version targeting the Engaged components (Engaged), or waitlist. Participants in active conditions were also randomized to receive phone coaching or just email prompts to increase program adherence. All three ACT conditions significantly improved over time relative to the waitlist condition on the primary outcome of mental health symptoms. The Engaged and Full conditions had greater rates of reliable change on the primary outcome relative to waitlist, but not the Open condition. Similarly, only Engaged and Full conditions improved on positive mental health relative to waitlist. The Full condition had greater improvements on a few ACT process measures relative to Engaged and Open conditions, particularly cognitive fusion. Overall, results indicate targeting only the Open components of ACT was somewhat less effective, and that including both the Open and Engaged components led to greater decreases in cognitive fusion. Highlights: Compared Full ACT website to Open components-only, Engaged-only, or waitlist. All 3 ACT conditions improved mental health symptoms relative to waitlist. Open condition equivalent to waitlist on reliable change and positive mental health. Full ACT improved more than Engaged or Open on cognitive fusion.